Synthesis and Structural Stability of α-Helical Gold(I)-Metallopeptidesy - Zengerling, Lydia; Kemper, Benedict; Hellmich, Ute A.; Besenius, Pol (Synlett, 2020)
The synthesis of hexa- and dodecapeptides functionalized with two Au(I)–phosphine complexes is reported. The high stability of the Au(I)–phosphine bond allowed orthogonal peptide-protecting-group chemistry, even when using hard Lewis acids like boron tribromide. This enabled the preparation of an Fmoc-protected lysine derivative carrying the Au(I) complex in a side chain, which was used in standard Fmoc-based solid-phase peptide synthesis protocols. Alanine and leucine repeats in the metallododecapeptide formed α-helical secondary structures in 2,2,2-trifluoroethanol–H2O and 1,1,1,3,3,3-hexafluoroisopropanol–H2O mixtures with high thermal stability, as shown by temperature-dependent CD spectroscopy studies.
Keywords: metallopeptides; gold complexes; peptide folding; α-helix; supramolecular chemistry; circular dichroism